2016
DOI: 10.1111/acv.12307
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor variation in the bottlenecked population of the endangered Seychelles warbler

Abstract: In small populations, drift results in a loss of genetic variation, which reduces adaptive evolutionary potential. Furthermore, the probability of consanguineous mating increases which may result in inbreeding depression. Under certain circumstances, balancing selection can counteract drift and maintain variation at key loci. Identifying such loci is important from a conservation perspective and may provide insight into how different evolutionary forces interact in small populations. Tolllike receptor (TLR) ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 142 publications
(147 reference statements)
4
37
0
Order By: Relevance
“…A previous study showed that five of seven TLR loci remained polymorphic in the Seychelles warbler population (Gilroy et al ., ,b). According to our simulations, we can reject neutral evolution for the three most polymorphic loci ( TLR1LB, TLR3 and TLR15; P < 0.001 for all), but not for the two less diverse loci ( TLR1LA and TLR5; P = 0.991, 0.964, respectively; Tables and ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study showed that five of seven TLR loci remained polymorphic in the Seychelles warbler population (Gilroy et al ., ,b). According to our simulations, we can reject neutral evolution for the three most polymorphic loci ( TLR1LB, TLR3 and TLR15; P < 0.001 for all), but not for the two less diverse loci ( TLR1LA and TLR5; P = 0.991, 0.964, respectively; Tables and ).…”
Section: Resultsmentioning
confidence: 99%
“…The following TLR loci were amplified: TLR1LA, TLR1LB, TLR3, TLR4, TLR5, TLR15 and TLR21, in 22‐30 individuals, as detailed in Gilroy et al . (,b).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations